Nitrate Sorption in an Agricultural Soil Profile - Wissem Hamdi; Faten Gamaoun; David E. Pelster; Mongi Seffen (Applied and Environmental Soil Science)
Increasing concentrations of in surface water and groundwater can cause ecological and public health effects and has come under increased scrutiny by both environmental scientists and regulatory agencies. For many regions though, including the Sahel of Tunisia, little is known about the sorption capacity of soils. In this project we measured sorption by a profile of an iso-humic soil from Chott Meriem, Tunisia. Soil samples were collected from four soil depths (0–25, 25–60, 60–90, and 90–120 cm) on 1 June 2011, and their sorption capacity was determined using batch experiments under laboratory conditions. The effects of contact time, the initial concentration, and the soil-solution ratio on sorption were investigated. In general, the results suggested that was weakly retained by the Chott Meriem soil profile. The quantity of sorption increased with depth, contact time, initial concentration, and soil-solution ratios. To evaluate the sorption capacities of the soil samples at concentrations ranging between 25 and 150 mg L−1 experimental data were fitted to both Freundlich and Langmuir isotherm sorption models. The results indicated that Freundlich model was better for describing sorption in this soil profile.